The Effectiveness of Self-Regulation Based Group Guidance in Reducing Students' Tendency Towards Excessive Digital Device Use - Firda Khoirotun Nisa; Chr. Argo Widiharto; Ellya Rakhmawati (Bulletin of Counseling and Psychotherapy, 2026)
Excessive digital device use has become an increasing concern among students due to its negative effects on concentration, social interaction, and self-regulation. This study investigated the effectiveness of self-regulation-based group guidance in reducing students' tendency toward excessive digital device use. A quantitative quasi-experimental pretest–posttest control-group design was employed involving 16 junior secondary school students, who were equally assigned to experimental and control groups. Data were collected using the Digital Device Use Tendency Scale (Cronbach's α = .931) and analysed using tests of normality and homogeneity, paired-samples t-tests, and independent-samples t-tests. The experimental group demonstrated greater improvement than the control group, as reflected in a higher normalized gain score (50.38% vs. 43.49%) and a statistically significant difference between groups (p = .039). These findings suggest that self-regulation-based group guidance is effective in reducing students' tendency toward excessive digital device use and offers a promising school-based preventive intervention for promoting healthier digital behavior.